Hydro-refining of coal-petroleum co-processing oil for potential clean jet fuels. (1st September 2022) - Shui, Hengfu; Ge, Rong; Zou, Dehai; Ren, Shibiao; Li, Zhanku; Yan, Jingchong; Lei, Zhiping; Wang, Zhicai
Highlights: CPCO could convert into clean fuels through hydro-refining and desulfurization. NiMoS/γ-Al2 O3 is reactive in desulfurization and hydrogenation. DF180 is more readily hydro-refined than CPCO for producing jet fuels. Hydro-refining of DF180 reduces sulfur meanwhile raises cyclanes content. Abstract: A coal-petroleum co-processing oil (CPCO) and its distillation fraction at 180 °C (DF180) were subjected to catalytic hydro-desulfurization and hydrogenation with batch autoclave and fixed bed reactor respectively to produce potential jet fuels with low sulfur and high cyclanes content. The results show that sulfur content of CPCO reaches up to 2282 mg/L. After fractionation through distillation, the sulfur content in DF180 is reduced to 283.6 mg/L. When CPCO was hydrogenated at 280 °C with NiMoS/γ-Al2 O3 catalyst, the content of sulfur-containing compounds (SCs) reduces and that of cyclanes increases. However, with higher hydrogenation temperatures or prolonged residence times, SCs content increased through their secondary reactions, i.e., the combination of S or HS with the fragments derived from hydro-cracking of CPCO. Meanwhile, the cyclanes content decreased. Similar phenomena were observed during hydrogenation of DF180 in autoclave. On the other hand, after 10 h continuous hydrogenation with NiMoS/γ-Al2 O3, the content of sulfur was reduced to 9.1 mg/L and that of cyclanes increased to 29.9%, thus meeting the requirements for clean jet fuels. From these perspectives, this work provides an alternative means for producing clean jet fuels with CPCO liquids.